Randomised double blind trial of oral versus intravenous flecainide for the cardioversion of acute atrial fibrillation. Issue 1 (1st July 2000) - Alp, N J; Bell, J A; Shahi, M
Abstract : OBJECTIVE: To investigate whether an oral loading dose of flecainide is as safe and effective as intravenous flecainide for the cardioversion of acute atrial fibrillation. DESIGN: Prospective, randomised, double blind, double placebo study. SETTING: Cardiac care unit of a large district general hospital in the UK. PATIENTS AND METHODS: 79 patients presenting with symptomatic acute atrial fibrillation: patients were given either intravenous flecainide (n = 39) or a solution of oral flecainide (n = 40), with appropriate placebos. All patients were heparinised during the study. PRIMARY OUTCOME MEASURES: Safety; mean time to cardioversion; proportion of patients restored to sinus rhythm at two hours and eight hours after treatment. Analysis was by intention to treat. RESULTS: There were no differences in baseline characteristics between the oral and intravenous groups. Both forms of flecainide were well tolerated, with no adverse clinical events during the study. The mean time to cardioversion was 110 minutes in the oral group and 52 minutes in the intravenous group (p = 0.002). Two hours after treatment, 27 of the 40 patients in the oral group (68%) and 25 of the 39 in the intravenous group (64%) had reverted to sinus rhythm (p = 0.74). Eight hours after treatment, 30 patients in the oral group (75%) and 28 in the intravenous group (72%) had reverted to sinus rhythm (p = 0.76). CONCLUSIONS: Intravenous flecainide restored sinus rhythm more rapidly than oral flecainide, but at two hours and eight hours after treatment there was no difference in the proportion of patients cardioverted by the two approaches. These results suggest a role for oral loading doses of flecainide in the treatment of acute or symptomatic paroxysmal atrial fibrillation.